Solitary Porokeratosis of Mibelli at an unusual site - Nithya Raghunath; Metikurke Vijayashankar (Our Dermatology Online, 2012)
Porokeratosis is an assorted group of five genetic disorders. These include porokeratosis of Mibelli, DSAP, punctate porokeratosis, porokeratosis palmaris et plantaris disseminata, and linear porokeratosis.They are disorders of abnormal keratinization characterized by the appearance of atrophic patches. Porokeratosis of Mibelli is referred to the more localized form of this disorder usually manifesting as solitary or a small group of lesions. It was first described by Mibelli in 1893 who described atrophic patches surrounded by a clinically and histologically unique ridge like border termed the cornoid lamella. The cornoid lamella is formed by rapidly proliferating atypical keratinocytes that expands peripherally to form a raised boundary at the junction of abnormal and normal cells. These lesions are most commonly found on the extremities, but can also be found on genitalia, face, oral mucosa and cornea. Though the patches are generally asymptomatic they can often lead to ulcerative, verrucous, giant, and malignant lesions. We describe a case of Porokeratosis of Mibelli at an unusual site in a 22 yr old male. The presenting history, clinical findings, biopsy results and available literature are reviewed.